Huge abdominal mass with hematocolpometra due to imperforate hymen: an unusual clinical presentation - Sharma, Basant; Khanal, Bandana; Singh, Prekshya; Tamrakar, Renuka (Journal of Chitwan Medical College, 2020)
The imperforated hymen is one of the commonest genital tract malformations usually present with cyclic abdominal pain and an obstructive pelvic mass at post-pubertal age. The unusual presentations are delayed menarche with obstructive symptoms rarely acute retention of urine, tenesmus, and constipation. We report an unusual case of 12- year old girl with a huge mass in the lower abdomen examination revealed imperforate hymen at early pubertal age. Further investigation of Magnetic Resonance Imaging (MRI) confirmed hematocolpometra. Then, she underwent simple hymenotomy and drainage of collected menstrual blood from the genital tract. She recovered well during the postoperative periods. We conformed normal menstrual flow at her first follow-up. In conclusion, Imperforate hymen at peripubertal age with an unusual huge abdominopelvic mass concerns further imaging to assure the best outcome.